DEVELOPMENT OF UKBI QUESTION BANK FOR STUDENTS OF THE INDONESIAN LANGUAGE STUDY PROGRAM - Nurkholidah, Riris; Faridah, Faridah; Indah Kusumawati, Tri (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
This study aims to develop and examine the validity, practicality, and effectiveness of a Question Bank for the Indonesian Language Proficiency Test (UKBI) for students of the Indonesian Language Education (Tadris Bahasa Indonesia) Study Program. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects comprised 35 sixth-semester students of the TBIND-1 class. Data were collected through expert validation sheets, lecturer and student response questionnaires, and learning implementation observation sheets. The results show that the developed UKBI question bank is valid, with a percentage of 80.76% in the media aspect and 88.46% in the learning evaluation aspect. The product’s practicality level based on student responses reached 87.75%, categorized as very practical. Meanwhile, the effectiveness level based on learning observation results achieved a percentage of 80.4%, categorized as effective. Therefore, the developed UKBI question bank is feasible to be used as a supporting instructional material to help students prepare for the UKBI and to support language learning in higher education.